Tanulmányaikat megszakítani kényszerülő hallgatók hazánk egyetemein az 1930-as évek derekán - Király, Sándor (Gerundium, 2011)
Concerning University Students Forced to Interrupt Their Studies in Hungary in the Middle of the 1930S. This study explores the reasons why in the 1930s—despite the general intent of support, a continuously developing student welfare institutional network, as well as the evolving state student social policy—led to a situation in which part of the university student body, owing to welfare conditions, was compelled to discontinue their studies. Those university students who—despite various support programs and because of their social conditions, the financial situation of their parents, high tuition fees, and perhaps because of further expenses pertaining to their studies—were unable to continue their studies, thus they were obliged to interrupt their university student status. Among the further possible causes for the termination of university studies reasons pertaining to health and actual study are also included, with the latter primarily meaning the absence of required preparedness. Statistical data provide a graphic representation of the situation of the university student population in Hungary in the middle of the 1930s.